The Director’s Story: iPads in the Directing Class - Costello, Jane (Proceedings of the International Conference on Networked Learning, 2012)
iPad technology emerged in the Spring of 2010. A tablet mobile technology, the iPad has generated considerable interest in higher education for teaching and learning. Any technology should be incorporated in teaching and learning because of its suitability to the learning event and context. Research on the use of iPads is needed to determine the success factors, potential pitfalls, and benefits. Students and instructor in a fourth year English directing class used iPads for course-related activities for one semester. Results of this case study’s video interview with the instructor, and co-investigator, are presented in this poster. The instructor, Yorick, discusses the benefits of the iPad and apps chosen, challenges encountered and how these were dealt with, and provides recommendations for others preparing to implement iPad technology in their networked learning course in higher education. The iPad increased communication, through sharing and collaboration, it was concise, portable, and made resources affordable and more accessible. Three terms are attributed to the iPad: organization, efficiency, and enthusiasm.